Cardiovascular drift and maximal oxygen uptake during running and cycling in the heat - Wingo, J. E.; Stone, T.; Ng, J. (Medicine & Science in Sports & Exercise, 2020)
Introduction: Greater cardiovascular (CV) drift occurs during cycling compared to running in temperate conditions. CV drift also corresponds to proportional reductions in maximal oxygen uptake (VO2max) during heat stress. Whether exercise mode differentially affects CV drift—and accompanying declines in VO2max—during heat stress is uncertain. The purpose of this study was to test the hypothesis that a greater magnitude of CV drift, accompanied by a greater decrement in VO2max, occurs during cycling compared to running in hot conditions. Methods: 7 active men (mean ± SD; age = 25 ± 6 yr, percent body fat = 11.9% ± 2.4%) completed a control graded exercise test (GXT) on a cycle ergometer and treadmill. Then on separate, counterbalanced occasions they completed 15 or 45 min of cycling or running at 60% VO2max in 35°C, immediately followed by a GXT to measure VO2max (4 trials total). The separate 15- and 45-min trials were designed to measure CV drift and VO2max over the same time interval. Results: Heart rate increased 19% and 17% and stroke volume decreased 20% and 15% between 15 and 45 min during running and cycling, respectively, but modes were not different (all P > 0.05). Despite a 1.8°C larger core-to-skin thermal gradient during running, decrements in VO2peak were not different between exercise modes (95% CI for difference in change scores between 15 and 45 min: -0.2, 0.3). Conclusions : CV strain (indexed as CV drift) during prolonged exercise in the heat corresponds to reduced VO2max, irrespective of exercise mode or the thermal gradient. As such, the upward drift in heart rate associated with CV drift reflects increased relative metabolic intensity (%VO2max) during prolonged cycling or running in the heat.